Introduction of Citizen Volpone & his Suite, at Paris. - Gillray, James, 1756-1815 (Humphrey, H., 1802)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Fox, Charles James, 1749-1806; Napoleon I, Emperor of the French, 1769-1821; Great Britain -- Politics and government -- 1800-1837